Evaluasi Dampak Pelatihan Pembuatan Lilin Aromaterapi Kopi Di Dusun Krajan - Dian Galuh Pratita; Erna Selviyanti; Sabran Sabran (Puslitbang Sinergis Asa Professional, 2022)
Community service activities are a form of tridharma in which information and skills are disseminated to the community. When the Covid-19 epidemic struck, individuals became highly concerned about their health, particularly about maintaining a healthy immune system to avert virus attacks. Various herbal products are widely utilized and freely available on the market. Herbal products are thought to be useful in reducing concern regarding the body's immunity. Aromatherapy candles are one of the efforts performed. Making aromatherapy candles out of coffee was one of the service activities carried out in Dusun Krajan. The goal of this study was to establish the respondents' level of autonomous application as a type of post-training evaluation. A descriptive strategy was adopted, with the target audience filling out a questionnaire. According to the findings of the analysis, 60% of the targets completed the application of creating aromatherapy candles independently after training, while 40% had not completed the application independently. Obstacles to obtaining raw materials and infrastructure were still felt by the respondents. Respondents believe there are no substantial impediments in terms of abilities.